Reimagining Obesity. Issue 2 (3rd April 2017) - Schultz, Jaime
ABSTRACT: This article draws on Mills' sociological imagination (from the 1959 publication The Sociological Imagination ) to consider the connections between personal trouble and social issues when it comes to the causes and consequences of obesity. These connections may be important for assuaging the "obesity bias" that pervades our discipline, particularly as it manifests in our undergraduate students and influences the ways they will act as future professionals.